Etika Bertetangga dalam Al-Qur’an Menurut Tafsir Al-Azhar Karya Hamka dan Relevansinya bagi Masyarakat Modern - Farhana Zulfa Azzahro; Muhammad Mukharom Ridho; Indri Astuti (BASHA'IR: JURNAL STUDI AL-QUR'AN DAN TAFSIR, 2025)
This study analyzes the values of neighborly ethics in Islam based on Prof. Dr. Hamka's interpretation in Tafsir Al-Azhar using a thematic interpretation approach and literature study. Neighborly ethics are understood not only as physical relationships but also encompass social and emotional aspects, including interactions with non-Muslim neighbors. Hamka interprets verses such as An-Nisa’ 36, An-Nahl 90, and Al-Ahzab 60–61, emphasizing the values of ihsan (doing good), ‘adl (justice), and ta’awun (mutual assistance) as concrete manifestations of faith with practical implications for maintaining social harmony, strengthening solidarity, and preventing conflict in a pluralistic society. The findings of this study indicate that Hamka’s ethics of neighborliness are contextual and remain relevant in the modern era, which tends to be individualistic. The practical implication is the need to revitalize the values of neighborly ethics through family education, social outreach, and community policies to build inclusive, tolerant, and just social relations, so that these teachings can serve as a guide to strengthen Islamic values and social resilience amid societal pluralism.